Augmented reality using features accelerated segment test for learning tajweed - Adi Putra Andriyandi; Wahyudin Darmalaksana; Dian Sa’adillah Maylawati; Ferli Septi Irwansyah; Teddy Mantoro; Muhammad Ali Ramdhani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Currently, education forms students to think creatively and critically, this can be supported by the multimedia technology for education, including Islamic religious education. Islam requires all of its Muslim to read the Qur'an. Tajweed is an important because it is related to the articulation of reading the Qur'an properly and correctly. This article discusses the application of augmented reality (AR) as one of the multimedia technologies that can be used as an interactive educational medium to help study the tajweed of Qur'an. The method used in this research is Features from accelerated segment test (FAST) corner detection. The testing result with 31 tajweed objects show that FAST is able to recognize all Tajweed objects and display their AR. Besides, based on a survey with questionnaires to several students, the result shows that 88.2% of students responded very well and judged that it was sufficient to help study the tajweed.